2017
DOI: 10.1155/2017/3756089
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PI3K p110αin the Adipose Tissue Results in Infertility and Delayed Puberty Onset in Male Mice

Abstract: Deletion of PI3K catalytic subunit p110α in adipose tissue (aP2-Cre/p110αflx/flx, α−/− hereafter) results in increased adiposity, glucose intolerance, and liver steatosis. Because this endocrine organ releases hormones like leptin, which are important in reproductive physiology, we investigated the reproductive phenotype of α−/− males. Compared to controls, α−/− males displayed delayed onset of puberty accompanied by a reduction in plasma LH levels and testicular weight. At postnatal day 30, α−/− mice exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
1
7
1
Order By: Relevance
“…Whether deletion of PI3K subunits in LR cells of peripheral tissues may have impacted the growth and reproductive phenotypes observed in our studies needs further evaluation. However, it should be noted that deletion of p110α only in adipocytes resulted in a very distinct phenotype compared to that observed in our studies, such that delayed puberty and infertility were observed only in male (not female) mice . The mechanism(s) associated with this phenotype remain unknown.…”
Section: Pros and Cons Of Using The Lr‐cre Line As A Metabolically Recontrasting
confidence: 66%
See 1 more Smart Citation
“…Whether deletion of PI3K subunits in LR cells of peripheral tissues may have impacted the growth and reproductive phenotypes observed in our studies needs further evaluation. However, it should be noted that deletion of p110α only in adipocytes resulted in a very distinct phenotype compared to that observed in our studies, such that delayed puberty and infertility were observed only in male (not female) mice . The mechanism(s) associated with this phenotype remain unknown.…”
Section: Pros and Cons Of Using The Lr‐cre Line As A Metabolically Recontrasting
confidence: 66%
“…However, it should be noted that deletion of p110α only in adipocytes resulted in a very distinct phenotype compared to that observed in our studies, such that delayed puberty and infertility were observed only in male (not female) mice. 104 The mechanism(s) associated with this phenotype remain unknown. Moreover, no reproductive or linear growth deficits have been described in mice with deletion of LR or disruption of PI3K class I in the liver.…”
Section: Pros and Con S Of Us Ing The Lr-cre Line A S A Me Taboli Cmentioning
confidence: 99%
“…The deterioration of reproductive functions was found in mice with a knockout of the gene encoding the catalytic p110α-subunit of PI3K in the adipose tissue [106]. In the testes of 30-day knockout mice with severe hyperleptinemia, the expression of the gene encoding leptin was increased, while the expression of the genes encoding StAR and P450 scc was reduced.…”
Section: Leptin Regulation Of the Male Gonadal Axis And Steroidogenesmentioning
confidence: 99%
“…Adult knockout mice had a severe form of hyperleptinemia, obesity, hepatic steatosis and the impaired glucose tolerance, and were infertile. It was quite unexpected that in the testes of knockout animals the expression of the ob gene and the Hsd17b3 gene encoding 17β-hydroxysteroid dehydrogenase 3 (17β-HSD) was significantly increased, and the plasma level of T was also increased, indicating a pronounced hyperandrogenemia [106]. A possible cause for this was the reduced activity of estrogen receptor-α (Esr1), since in animals lacking the Esr1 gene a similar phenotype with hyperandrogenemia and infertility was described [107,108].…”
Section: Leptin Regulation Of the Male Gonadal Axis And Steroidogenesmentioning
confidence: 99%
“…The onset of puberty is also gated by body energy reserves and nutritional cues (Vazquez, Velasco, & Tena‐Sempere, 2019), and in which, the adipose hormone leptin is an essential signal to the hypothalamic GnRH pulse generator that there are sufficient energy stores in the adipose tissue for fertility to commence, which is necessary for the initiation of puberty (Ahmed, Ong, & Dunger, 2009; Biro, Khoury, & Morrison, 2006; Egan, Inglis, & Anderson, 2017). Leptin stimulates GnRH secretion by binding to the leptin receptor to activates several signaling pathways, including the 5′ adenosine monophosphate‐activated protein kinase (Roa et al, 2018; Xie et al, 2018), mammalian target of rapamycin (mTOR; Roa & Tena‐Sempere, 2010; Roa et al, 2009), phosphoinositide 3‐kinase (PI3K; Garcia‐Galiano, Borges, Allen, & Elias, 2019; Garcia‐Galiano et al, 2017; Nelson et al, 2017; Nguyen, Zacchi, Schulz, Moore, & Fortes, 2018).…”
Section: Summary and Future Directionsmentioning
confidence: 99%